PRODUK DIVERSIFIKASI GERIT JAGUNG HASIL OLAHAN WARGA DESA DUWET KECAMATAN TUMPANG – KAB. MALANG - Ayu Sulasari; Tri Yulisyawati Evelina; Ellyn Eka Wahyu; Ita Rifiani Permatasari; Yekie Senja Oktora; Jatrifia Ongga Sinatrya (Publisher UPT P2M Politeknik Negeri Malang, 2022)
This program aims to provide agricultural product processing technology in Duwet, Petungsewu – Malang. The activities carried out are processing corn kernels into tortilla chips and to provide knowledge about entrepreneurship, so that the partner village communities are able to manage their businesses, and improve the empowerment of business groups well. The method of this program are carried out in several stages, namely the initiation of the object of program, coordination with the community as the object of program, implementation of program, and evaluation of activities. Based on the results of the activity, there was a change in behavior to be more creative and innovative in processing corn kernels into Dupitos products (the name of the corn chips product) so as to increase the selling value of products to SME partners.